Anaesthetic Considerations In Elderly - TEENA BANSAL,; NAVEEN MALHOTRA,; SARLA HOODA, (International Journal of Pharma and Bio Sciences, 2012)
Aging is a universal physiological process clinically characterized by degenerative changes in the structure and function of various organs. Geriatric patients are more sensitive to various anaesthetic drugs. Age alters both pharmacokinetic and pharmacodynamic aspects of anaesthetic management. The most important objective of perioperative care of geriatric population is to speed recovery and avoid functional decline. Compensation for age-related changes is usually adequate, but limitation of physiological reserve is evident during times of stress during anaesthesia and surgery.